Keanekaragaman Kupu-Kupu (Lepidoptera) dan Tumbuhan Pakannya di Kawasan Hutan Dengan Tujuan Khusus (KHDTK) UIN KHAS Jember - Mubarok, Husni; Nuruzzaman, Adzkafillah; Fitriyah, Haniatul; Qodri, Agmal (Berkala Ilmiah Biologi, 2025)
Butterflies (Lepidoptera) are essential pollinators and bioindicators of environmental quality. The Forest Area for Special Purposes (KHDTK) of UIN KHAS Jember has experienced forest conversion into agricultural and vegetable cultivation areas, raising the need for biodiversity data to inform management strategies. This study examined butterfly diversity and their host plants through field surveys using an exploration method. A total of 546 individuals representing 31 species from five families were recorded, with Nymphalidae as the most abundant family and Eurema hecabe and Ypthima pandocus as dominant species. The diversity index indicated a moderate level (H’=2.45), accompanied by low evenness (E=0.37) and high dominance (D=0.87). In addition, 20 host plant species from 12 families were identified, with Asteraceae and Verbenaceae being the most prominent. The findings reveal that despite habitat fragmentation, KHDTK UIN KHAS Jember functions as an important butterfly habitat, underscoring the urgency of conservation efforts through host plant enrichment and sustainable vegetation management to preserve pollinator community stability.